Relevansi Pendekatan Deep Learning Berbasis Cultural Neuroscience untuk Meningkatkan Kompetensi Pembelajaran Agama Islam - Muhammad Danial; Rukaya Rukaya; Alfaridzi Hamsudi (FASTABIQ: JURNAL STUDI ISLAM, 2025)
The limited internalization of religious values and information in Islamic Religious Education learning in schools is often caused by insufficient consideration of neuroscience and cultural aspects in the learning process. This research aims to discover an appropriate Islamic Religious Education learning model with a Deep Learning approach that aligns with efforts to strengthen cultural values embedded in the learning process, adapting this learning model in Islamic Religious Education with a cultural approach implemented based on neuroscience knowledge. This research employs a mixed methods research model, utilizing qualitative data with a phenomenological approach to identify students' learning style tendencies in schools, while quantitative data is used to confirm and test findings from the qualitative data. The results of this research demonstrate that 1) the three dimensions of the deep learning approach are interconnected and influence Islamic Religious Education learning at every educational level, 2) adapting the Deep Learning approach based on Cultural Neuroscience into the learning process supports the existence of cultural values in learning implementation, 3) the implementation of Islamic Religious Education learning through the Deep Learning approach with the Cultural Neuroscience concept not only has implications for improving Islamic Religious Education learning competencies, but also for developing cognitive abilities and students' capacity to contextualize Islamic Religious Education learning.